COMPARISON MUT'AH MARRIAGE ACCORDING TO ISLAMIC LAW AND NATIONAL LAW - Idrus Umarama; Agus Hamzah; Jamaludin Al Ashari; Arie Widyantoro; Faradina Mar’atus Shofia (UNISSULA, 2020)
Mut'ah marriage or temporary marriage or what is known as contract marriage is a phenomenon that often occurs in Indonesia, this problem must be anticipated because it is detrimental to women and has been forbidden by the Indonesian Ulama Council. The research method used is a normative juridical approach. Normative research or also known as literature law research is legal research carried out by examining library materials or secondary data. The results of the research found stated that Mut’ah marriage is temporary marriage, the Prophet Muhammmad S.A.W has justified the mut’ah marriage for three days and after that the Prophet forbade it forever. Here the Apostle once allowed it at a time which might have taken the form of an emergency as it was permissible to eat carcass meat, if there were no other foods under compulsion.